2022
DOI: 10.3389/fchem.2022.867928
|View full text |Cite
|
Sign up to set email alerts
|

Self-Masked Aldehyde Inhibitors of Human Cathepsin L Are Potent Anti-CoV-2 Agents

Abstract: Cysteine proteases comprise an important class of drug targets, especially for infectious diseases such as Chagas disease (cruzain) and COVID-19 (3CL protease, cathepsin L). Peptide aldehydes have proven to be potent inhibitors for all of these proteases. However, the intrinsic, high electrophilicity of the aldehyde group is associated with safety concerns and metabolic instability, limiting the use of aldehyde inhibitors as drugs. We have developed a novel class of compounds, self-masked aldehyde inhibitors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…287 Additionally, some of the selfmasked aldehyde inhibitors of cruzain, the main protease of Trypanosoma cruzi, were also tested against SARS-CoV-2 (vide infra). 288,289 Beyond aldehydes, many other well-known types of carbonyl-derived warheads have been employed to target the SARS-CoV-2 M pro , including α-ketoamides, 290 ketobenzothiazoles 291,292 and α-acyloxymethyl ketones 293 (see also section 2.6.3) but also nitriles. 294,295 However, an extensive discussion of them is out of the scope of this Perspective, and the reader is referred to the cited publications.…”
Section: Cysteine Targeting By Reversible S N Ar Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…287 Additionally, some of the selfmasked aldehyde inhibitors of cruzain, the main protease of Trypanosoma cruzi, were also tested against SARS-CoV-2 (vide infra). 288,289 Beyond aldehydes, many other well-known types of carbonyl-derived warheads have been employed to target the SARS-CoV-2 M pro , including α-ketoamides, 290 ketobenzothiazoles 291,292 and α-acyloxymethyl ketones 293 (see also section 2.6.3) but also nitriles. 294,295 However, an extensive discussion of them is out of the scope of this Perspective, and the reader is referred to the cited publications.…”
Section: Cysteine Targeting By Reversible S N Ar Reactionsmentioning
confidence: 99%
“…Further aldehyde derivatives based on the bicyclic core scaffold of the approved antiviral drugs boceprevir or telaprevir, such as 148 and 149 (Figure ), were also developed using a similar covalent design strategy to obtain a good PK profile in rats . Additionally, some of the self-masked aldehyde inhibitors of cruzain, the main protease of Trypanosoma cruzi , were also tested against SARS-CoV-2 ( vide infra ). , Beyond aldehydes, many other well-known types of carbonyl-derived warheads have been employed to target the SARS-CoV-2 M pro , including α-keto­amides, keto­benzo­thiazoles , and α-acyloxy­methyl ketones (see also section ) but also nitriles. , However, an extensive discussion of them is out of the scope of this Perspective, and the reader is referred to the cited publications.…”
Section: Targeting the Cysteine Side Chainmentioning
confidence: 99%
“…The authors have found that 29 is a selective inhibitor of CatL, with higher inactivation rates of the latter than cathepsins B and K, and it inhibits viral entry in four host cells models (Vero E6, HeLa/ACE2, A549/ACE2 and Calu-3/2B4) with nanomolar potency. Following these results, Zhu et al aimed to develop a series of SMAIs that could inhibit both CatL and SARS-CoV-2 M pro [ 126 ] by finding a unique peptide scaffold that would be recognized by both proteases. Although none of the compounds were able to inhibit M pro directly, they found that some of the SMAIs were able to produce an inhibition of the cytopathic effect on Vero E6 and A549/ACE2 cells infected with SARS-CoV-2, indicating that a bi-functional strategy might be feasible with proper optimization, while also indicating that targeting the host’s proteases is also a possible strategy to prevent viral infection.…”
Section: Host Proteases As Potential Drug Targets For Antiviral Thera...mentioning
confidence: 99%
“…Zhu J. et al investigated a potential anti-SARS-CoV-2 activity of a novel class of self-masked aldehyde inhibitors (SMAIs). They characterized the human cathepsin L inhibition of these compounds and found that propargyl analogue of K777 significantly blocked the SARS-CoV-2-induced cytopathic effect in Vero E6 and A549/ACE2 cells [ 79 ]. A therapeutic approach leading to a decreased infection rate and improved efficacy could be a synergistic block of crucial factors in the viral replication cycle.…”
Section: Preclinical Studiesmentioning
confidence: 99%